IN-FLIGHT ABSOLUTE CALIBRATION OF CBERS SENSORS - Flávio Jorge Ponzoni; José Carlos Neves Epiphanio (Revista Brasileira de Cartografia, 2013)
The National Institute for Space Research (INPE) decided to freely distribute the orbital images available on its own catalog since the beginning of the last decade. One of the most important consequences of that decision has been the wide usage of the remote sensing technology among different Brazilian user profile, including students, private companies and scientific academies. Besides that, the China-Brazil Earth Resources Satellite (CBERS) program has opened several applications and research possibilities to the Brazilian community, which have not been restricted to mapping or qualitative information extraction from the images, but including quantitative approaches that need an accurate link between the images digital numbers and the effective in-flight radiance measured by the CBERS sensors. This link is established by the so called "absolute calibration" that can be performed before launch and during the flight by internal system or by procedures conducted on the Earth surface (external to the satellite). This last possibility has been carried out on reference surfaces such as those endorsed by the Committee on Earth Observation Satellites (CEOS) that basically are located in desert regions of the planet. The Brazilian territory does not have desert surfaces or any one CEOS endorsed surface, but in-flight calibration campaigns have been performed using agricultural crops surfaces located in the northeast region of the country whose results have been comparable with those achieved internationally. The objective of this chapter is to describe the main CBERS sensors absolute calibration procedures that have been adopted in Brazil.